Unveiling Entrepreneurial Learning Dynamics: Insights from the Women Entrepreneurs of Creative Industries - Abrar , Ayesha; Gohar, Madiha; Malik , Fareesa; Golra , Owais Anwar (Journal of Innovative Research in Management Sciences, 2024)
Purpose –This research aims to explore social learning aspects of entrepreneurial learning within the creative industries. The creative industries produce customised products, where creative entrepreneurs co-create goods according to the customer’s preferences. The entrepreneurial learning literature includes empirical and theoretical studies from different industry sectors. However, little attention is evident in the entrepreneurship research from the creative industries. The limited literature on entrepreneurial learning in the creative industries indicates that creative industries entrepreneurs rarely pursue formal education to enhance their skills and knowledge. Instead, their business learning is deeply rooted in the social, cultural, and economic contexts of the real world in which they are situated. These brief findings demand an in-depth exploration of entrepreneurial learning processes and sources within the creative industries context.Design/methodology/approach – This empirical study is based on qualitative research, employing in-depth case studies of creative industries entrepreneurs. The data was collected through semi-structured interviews with women entrepreneurs who work as designers in the creative industries. To analyze the data, a cross-case comparison was conducted, along with the use of grounded theory techniques.Findings – The findings highlight that entrepreneurial learning is a dynamic process where the interaction of personal and social experiences of entrepreneurs during their entrepreneurial journey is of utmost importance. This learning process involves activities such as observing, practices, doing, trial and error, and constant interaction with the entrepreneurial community. Furthermore, understanding the learning process relies largely on the contextual environment. Creative industries’ entrepreneurs employ the variety of sources for learning, out of which personal networks (family, friends, etc.) and technological resources (internet, software) are vital. Social media also plays a significant role in their learning process, as it serves as a valuable source of information and learning.Implications – The study improves our understanding of how women entrepreneurs engage in entrepreneurial learning within a specific industry and social context. Furthermore, the research identifies the challenges that are critical to address through entrepreneurship education and support organizations – that cater to community entrepreneurs.Originality/value – The literature has acknowledged the strong influence of cultural and social context on women entrepreneurs, particularly in developing countries. This research contributes to the limited body of knowledge on entrepreneurial learning among women creative entrepreneurs by exploring the interplay between personal and social learning experiences along with multiple contextual forces.